Teacher Strategies and Parental Involvement in Supporting the Transition from Early Childhood Education to Primary School in West Java: A Survey Study - Susan Maulani; Shinta Mutiara Puspita; Agus Ruswandi; Cucu Susanti; Widya Tasya Astiti; Siti Nasriatul Hamidah; Nailal Munayah (MASI Mandiri Edukasi, 2026)
The transition from early childhood education to primary school remains a critical yet underexamined phase, particularly in contexts where school readiness is narrowly defined in academic terms. Despite increasing attention to early childhood education, limited research has explored how teacher strategies and parental involvement jointly shape children’s transition. This study aims to examine the strategies employed by PAUD teachers and the role of parental involvement in supporting children’s transition to primary school in West Java. A cross-sectional survey was conducted involving 132 teachers and 182 parents. Data were analyzed using descriptive statistics and the Kruskal–Wallis H test. Findings indicate that teachers predominantly implement classroom-based strategies focused on pre-literacy, numeracy, behavioral regulation, and independence. However, these practices are more strongly influenced by parental expectations for early academic achievement than by child-centered pedagogical approaches. Collaboration between early childhood and primary school teachers remains limited, contributing to a fragmented understanding of school readiness. Parental involvement is largely home-based, with relatively low participation in school-based programs. These findings highlight the need for structured institutional collaboration and more balanced approaches to school readiness that integrate academic and developmental dimensions to support children’s holistic transition.